Multimorbidity patterns in South Africa: A latent class analysis - Roomaney, Rifqah Abeeda; van Wyk, Brian; Cois, Annibale; Pillay van-Wyk, Victoria (Frontiers in Public Health, 2023)
Introduction: South Africa has the largest burden of HIV worldwide and has a growing burden of non-communicable diseases; the combination of which may lead to diseases clustering in ways that are not seen in other regions. This study sought to identify common disease classes and sociodemographic and lifestyle factors associated with each disease class. Methods: Data were analysed from the South African Demographic Health Survey 2016. A latent class analysis was conducted using nine disease conditions. Sociodemographic and behavioural factors associated with each disease cluster were explored. All analysis was conducted in Stata 15 and the LCA Stata plugin was used to conduct the latent class and regression analysis. Results: Multimorbid participants were included (n = 2 368). Four disease classes were identified: HIV, Hypertension and Anaemia (comprising 39.4% of the multimorbid population), Anaemia and Hypertension (23.7%), Cardiovascular-related (19.9%) and Diabetes and Hypertension (17.0%). Conclusion: This study affirmed that integrated care is urgently needed, evidenced by the largest disease class being an overlap of chronic infectious diseases and non-communicable diseases. This study also highlighted the need for hypertension to be addressed. Tackling the risk factors associated with hypertension could avert an epidemic of multimorbidity.